A STUDY OF NORMAL ANATOMY OF HARD PALATE IN SOUTH INDIAN POPULATION - DR. VINODINI LAKMALA, M.D,; DR. RAJA REDDY GANGAM, M.D,; DR. PRAVEENA NAGARAJU, M.D, (International Journal of Pharma and Bio Sciences, 2016)
The hard palate is an essential part of human skull. It forms the roof of the mouth and floor of nasal cavities. The detailed knowledge of hard palate plays an important role in the passive articulation of speech. The present study was conducted on 30 skulls of which 17 were male cases and 13 female cases collected from the department of Anatomy, Gandhi Medical College, Secunderabad, Telangana state, India. The measurements of palatine length, breadth and height were recorded. Palatine index and palatine height index were calculated using standard formulae. Mean palatine length in male and female cases were 54.18 and 48.0mm respectively. Mean palatine breadth was 34.0 and 32.54mm and height 15.76 and 13.15mm respectively. Mean palatal length showed a highly significant difference between male and female cases. Palatal breadth and height showed no significant difference between both sexes. However, the average values of palatine length, breadth and height in male cases were higher compared to female cases. Palatal Index and Palatal Height Index showed no significant differences between both genders.